PENGGUNAAN MEMBRAN KITOSAN UNTUK MENURUNKAN KADAR LOGAM KROM PADA LIMBAH INDUSTRI PENYAMAKAN KULIT - Sholeh Ma’mun; Marhaenia Theresa; Sarah Alfimona (Teknoin, 2016)
Membrane made of chitosan from shrimp shell can be used to reducea heavy metal chromium (Cr) content in leathertanning industry waste by adsorption. The membranes were manufactured from chitosan with concentrations of 2, 3, and 4wt%, respectively. In addition, glycerol was added during membrane manufacturing as an additive to increase the permeability properties. The results showed that themembrane with 2% chitosan without glycerol gave the best adsorption performance. However, increased the chitosan concentration showed a negative effect to the membrane performance in adsorbing the chromium due to chitosan solubility limitation in the acetic acid. However, the use of glycerol did not improve the adsorption performance. This was due to hydrophilic property of the glycerol.